1998
DOI: 10.1055/s-2007-1001312
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Controlled Sedation with Propofol and Alfentanil During Colonoscopy: A Pilot Study

Abstract: PCS with propofol and alfentanil is an effective, short-acting form of sedation for patients undergoing colonoscopy and may be an alternative to benzodiazepines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…2 It provides faster onset of sedation and rapid recovery of cognitive function. 3,4 Propofol can be given alone 3,5,6 or in combination with an opioid [7][8][9][10][11] or a benzodiazepine. 4,12,13 Compared with propofol alone, the combined regimens can reduce doses of propofol in most studies.…”
mentioning
confidence: 99%
“…2 It provides faster onset of sedation and rapid recovery of cognitive function. 3,4 Propofol can be given alone 3,5,6 or in combination with an opioid [7][8][9][10][11] or a benzodiazepine. 4,12,13 Compared with propofol alone, the combined regimens can reduce doses of propofol in most studies.…”
mentioning
confidence: 99%
“…Time from start of sedation to start of procedure; min 8.9 (4.8)[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Duration of procedure; min 15.6 (7.9) [1-39] Time from start of sedation to discharge; min 39.5 (9.6) [20-63] Time from end of procedure to discharge; min15Histogram showing the lowest recorded oxygen saturations.…”
mentioning
confidence: 99%
“…Remifentanil and propofol have similar pharmacokinetic profiles, making them the most suitable drugs for use in a PCS system. PCS without background infusion has been assessed to be successful using propofol alone or mixed with alfentanil during colonoscopy and cataract surgery (5–7). Blair et al (8) demonstrated that auto‐administered boluses of remifentanil without background infusion may safely provide worthwhile labour analgesia, and that adding a continuous infusion to the auto‐administered boluses did not result in any further significant reduction in pain scores.…”
mentioning
confidence: 99%